Spectral decomposition of a long Rossby wave after reflection on an equatorial western boundary - Camerlengo, Alejandro L. (1997)
This study addresses the evolution of a single Rossby wave in the wave number space. Due to its simplicity, as compared to the reflection at the equatorial eastern boundary, the analytical and numerical problem of the reflection of the long Rossby wave at the western boundary is chosen. The main results of this investigation are: 1) the solution in the wave number space is similar to the one in the original wave pattern field, although their physical interpretation is completely different; 2) the interpretation of the spectrum is fairly more simple than the analysis of the original wave pattern field.